2021
DOI: 10.23937/2469-5823/1510158
|View full text |Cite
|
Sign up to set email alerts
|

Views of Nursing Students Who Have Experienced Caring for Psychiatric Patients on Mental Illness and Stigma: A Phenomenological Study

Abstract: Aim: To explore the views of nursing students who have experienced caring for psychiatric patients on mental illness and stigma. Methods:The phenomenological method was used in the study as the qualitative research design. The research was conducted with 23 students who completed the theoretical part of the psychiatric nursing course and its clinical practice in the nursing department of a university in Turkey. The data were collected through individual in-depth interviews and analyzed by content analysis meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…They also had a more advanced understanding of the importance of stigma. In addition, they stated that there was a change in their view of patients and diseases [ 20 ]. One study also showed that with time on a clinical internship, students considered people with mental disorders to be less dangerous [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…They also had a more advanced understanding of the importance of stigma. In addition, they stated that there was a change in their view of patients and diseases [ 20 ]. One study also showed that with time on a clinical internship, students considered people with mental disorders to be less dangerous [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Students in the study conducted by Başoğul (2021) also stated that these patients are marginalized, ridiculed, and treated as if they are different from others. These students used words such as confinement in society, difficulty, difference, unluckiness, lostness, derangement, obscurity, and innocence to explain mental illness [ 20 ]. Some studies have also used the metaphor of “a fragmented entity” to describe patients with depression [ 49 ] and schizophrenia [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations